Analysis of the Level of Sharia Financial Literacy in Muslim Msmes in the Aloon-Aloon Area of Lamongan Regency - Tsaniah Lailatul Arofah; Akmalur Rijal; Luthfillah, Mohammad (Jurnal Multidisiplin Sahombu, 2025)
This research is entitled Analysis of Sharia Financial Literacy Levels in Moslem UMKM in the Alun-Alun Area of Lamongan Regency using qualitative field research and methods and descriptive analysis, the aim of this research is to find out level of sharia financial literacy among Moslem UMKM in the Lamongan Regency square area. The results of this research show that the sharia financial literacy level of moslem UMKM in the Lamongan Regency square area is classified as less literate with an average percentage of 71/7%. This study uses 4 dimensions, namely basic knowledge of sharia finance, share savings and loans, sharia insurance and sharia investment, with average results in each aspect, namely : basic knowledge of sharia finance 84%, sharia savings and loans 62.7%, sharia insurance 68% and sharia investment 72%.